Profil Kualitas Mikroskopis Sediaan Hepar Mencit (Mus musculus) dengan Pemotongan Ketebalan 2µm, 5µm dan 8µm - Mircha Restiana Elen (Jaringan Laboratorium Medis, 2022)
The cutting stage is the network manufacturing stage which needs to be considered the thickness scale. The standard scale that is commonly used is 2-7 µm, while the thickness of 5 µm which is used as a standard for cutting the thickness of the liver tissue shows that the cell is good for cutting liver tissue in mice (Mus musculus). Mice have many advantages, while the liver organ is one of the organs that are often used in research. The aim of this study was to describe the microscopic quality of liver preparations of mice (Mus musculus) by cutting tissue thickness of 2 µm, 5 µm and 8 µm. This type of research includes experimental research with descriptive research criteria. The study design used a purposive sampling study approach. The results of the quality of microscopic images of mice tissue (Mus musculus) at a thickness of 2 µm there were 12% not good, 20% not good and 68% good. The thickness of 5 µm is 100% good, while the thickness of 8 µm is 8%, the preparation is not good,  36% is not good, and 56% is good. The conclusions of this study were microscopic tissue mice (Mus musculus) preparations with good quality 68%, 8 µm 56%, and 100% at a thickness of 5 µm.